2014
DOI: 10.1130/b30979.1
|View full text |Cite
|
Sign up to set email alerts
|

Postglacial denudation of western Tibetan Plateau margin outpaced by long-term exhumation

Abstract: The Indus River, one of Asia's premier rivers , drains the western Tibetan Plateau and the Nanga Parbat syntaxis. These two areas juxtapose some of the lowest and highest topographic relief and commensurate denudation rates in the Himalaya-Tibet orogen, respectively, yet the spatial pattern of denudation rates upstream of the syntaxis remains largely unclear, as does the way in which major rivers drive headward incision into the Tibetan Plateau. We report a new inventory of 10 Be-based basinwide denudation rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 72 publications
(83 reference statements)
3
35
0
Order By: Relevance
“…Munack et al . [] found that 10 Be data from the Indus valley, along the southern margin of the Ladakh Range, spanning postglacial timescales of 10 3 –10 4 years, indicate denudation rates of only 0.01–0.11 mm yr −1 . As these rates are lower than those derived from low‐temperature thermochronological data spanning greater timescales of >10 6 years (approximately 0.1–0.4 mm yr −1 ) [ Clift et al ., ; Kirstein et al ., , ; Kirstein , ; Kumar et al ., ; Sinclair and Jaffey , , this study], the authors concluded that glacial processes during previous glacial cycles must have made a significant contribution to erosional denudation and rock exhumation and cooling.…”
Section: Discussionmentioning
confidence: 99%
“…Munack et al . [] found that 10 Be data from the Indus valley, along the southern margin of the Ladakh Range, spanning postglacial timescales of 10 3 –10 4 years, indicate denudation rates of only 0.01–0.11 mm yr −1 . As these rates are lower than those derived from low‐temperature thermochronological data spanning greater timescales of >10 6 years (approximately 0.1–0.4 mm yr −1 ) [ Clift et al ., ; Kirstein et al ., , ; Kirstein , ; Kumar et al ., ; Sinclair and Jaffey , , this study], the authors concluded that glacial processes during previous glacial cycles must have made a significant contribution to erosional denudation and rock exhumation and cooling.…”
Section: Discussionmentioning
confidence: 99%
“…1, Table 1) fit the picture of very slow landscape lowering in the upper Indus basin (Dortch et al, 2011;Munack et al, 2014 (Fig. 1), which we expected to denude faster following river capture ~135 ka ago.…”
Section: Catchment Denudation and Recycling Of Pleistocene Sedimentsmentioning
confidence: 98%
“…Denudation rates along the Indus drop from >1000 mm ka -1 near the syntaxis (Burbank et al, 1996) to ~10 mm ka -1 at the western Tibetan Plateau margin . Denudation rates estimated from cosmogenic 10 Be inventories are low despite the steep alpine topography (Dortch et al, 2011;Dietsch et al, 2014;Munack et al, 2014), so that the Transhimalayan ranges of Ladakh and Zanskar host some of the oldest glacial landforms in the Himalaya-Tibet orogen Hedrick et al, 2011). Massive staircases of river-derived fill terraces (Fort et al, 1989;Clift and Giosan, 2014) located up to 400 m above present river levels, together with stacks of lake sediments and local landslide and fan deposits (Hewitt, 2002;Phartiyal et al, 2005; 2013), testify to major alternating cut-and-fill cycles in the upper Indus catchment (Blöthe et al, 2014).…”
Section: Study Areamentioning
confidence: 99%
“…We note that several other 10 Be data sets from the Himalaya were published after we had assembled the data set used in this study. They cover study areas in Ladakh [Munack et al, 2014;Dietsch et al, 2015], Bhutan [Portenga et al, 2015;Le Roux-Mallouf et al, 2015;Adams et al, 2016], Garhwal [Morrell et al, 2015], eastern Nepal [Olen et al, 2015], Sikkim [Abrahami et al, 2016], and Himashal Pradesh [Olen et al, 2016]. The data from Ladakh would be difficult to include in our analysis due to the lack of discharge data from this arid region.…”
Section: 1002/2016jf004011mentioning
confidence: 99%